고추 풋마름병에 대한 효율적인 저항성 검정법 확립 - 황성민(Sung Min Hwang); 장경수(Kyoung Soo Jang); 최용호(Yong Ho Choi); 김헌(Hun Kim); 최경자(Gyung Ja Choi) (Sigmulbyeong yeon'gu, 2017)
Bacterial wilt caused by Ralstonia solanacearum is an important disease in cultivation of chili pepper, causing plant death and significant yield losses. Cultivation of disease-resistant varieties is the most suitable measure to control bacterial wilt of chili pepper. To establish an efficient screening method for resistant chili pepper to R. solanacearum, six resistant or susceptible cultivars to the R. solanacearum were selected and the development of bacterial wilt on the cultivars according to several conditions was investigated. Drenching bacterial suspension into the cut roots using a scalpel was more simple and effective to distinguish resistant and susceptible cultivars than inoculation methods of root-dipping or soil-drenching without wounding. A resistant pepper, 'MC4' to R. solanacearum showed high resistance under the developed conditions which were 21- to 28-day-old pepper inoculated with $1{×}10^8cfu/ml$ of bacterial suspension. On the other hands, the susceptible cultivars represented high disease severity under the conditions. These results indicated that we developed an efficient method to evaluate resistance of chili pepper cultivars against bacterial wilt. In addition, we successfully evaluated resistance degree of 140 commercial chili pepper cultivars to R. solanacearum using the developed method. Ralstonia solanacearum에 의한 고추 풋마름병은 고추의 생산량 감소에 영향을 미치는 주요 병해 중 하나이다. 그리고 병 저항성 작물을 재배하는 것은 고추의 풋마름병 방제에 가장 효과적인 방제 방법이다. 본 연구는 고추의 풋마름병 저항성을 효율적으로 검정하기 위한 방법을 개발하기 위하여 수행되었다. 풋마름병에 대한 저항성 및 감수성 6개 고추 품종을 선발하고, 다양한 조건에서 이들 품종의 풋마름병 발생을 조사하였다. 접종 방법에 따른 고추 품종들의 풋마름병 발생 정도를 실험한 결과, 상처없이 토양관주하는 방법과 접종원에 뿌리를 침지하는 방법보다 뿌리 절단 후 접종원을 관주하는 방법이 더 간단하고 효율적이었다. 풋마름병 저항성 계통인 'MC4'는 파종 후 21일부터 28일 재배한 고추 유묘에 $1{×}10^8cfu/ml$ 농도의 세균 현탁액을 포트 당 20 ml 접종하였을 때 가장 높은 저항성을 나타냈다. 한편 감수성 품종들은 이들 조건에서 높은 감수성을 보였다. 이들 결과는 우리가 고추 품종의 풋마름병에 대한 효율적인 저항성 검정방법을 개발하였다는 것을 나타낸다. 그리고 선발한 발병조건을 사용하여 시판중인 140개 고추 품종의 풋마름병에 대한 저항성 정도를 평가하였다.